The strengths and limits of cannabinoids and their receptors in cancer: Insights into the role of tumorigenesis-underlying mechanisms and therapeutic aspects - Fatemeh Hosami (Elsevier, 2021)
Cancer, as a mysterious and complex disease, has a multi-stage molecular process that uses the cellular molecular machine and multiple signaling pathways to its advantage. Cannabinoids, as terpenophenolic compounds and their derivatives, showed influences on immune system responses, inflammation, and cell growth that have sparked a growing interest in exploring their effects on cancer cell fate, as well. A large body of evidence in experimental models indicating the involvement of cannabinoids and their related receptors in cancer cell growth, development, and fate. In accordance, the present study provided insights regarding the strengths and limits of cannabinoids and their receptors in critical steps of tumorigenesis and its underlying molecular pathways such as; cancer cell proliferation, type of cell death pathway, angiogenesis, invasion, metastasis and, immune system response. Based on the results of the present study and due to the contribution of cannabinoids in various cancer cell growth control processes, these compounds cancer can be considered worthwhile in finding new alternatives for cancer therapy.